Post-enucleation Functional Vision Assessment in Retinoblastoma Survivors. A neglected aspect in management plan! 10.36351/pjo.v39i3.1673 - Chaudhary, Shabana (Pakistan Journal of Ophthalmology, 2023)
Little is known about the impact of treatment in retinoblastoma (RB) survivors in terms of disabilities which may cause hindrance in taking part in daily life activities. van Dijk et al reported that 55% of the RB survivors perceive RB-related restrictions in their routine life activities related to their school, professional career, mobility, or self-care, etc.1 Weintraub and colleagues also found a negative correlations between motor functions and children's quality of life (QOL) who survived RB treatmentand have monocular vision.2